(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Cooking education in junior high school relies heavily on the quality of resources and environments that support hands-on learning. This study examined the effects of cooking facilities, laboratory environment, teacher supervision, and sustainability awareness on the cooking performance of Grade 9 students enrolled in the TLE–Cookery specialization. Using a descriptive-correlational design, data were gathered from 200 students in two national high schools in District 2, Bukidnon through a validated and reliable questionnaire and an actual performance rubric anchored on the TLE Cookery curriculum. Ethical approval, administrative permission, parental consent, and student assent were secured before administering the instruments. Findings showed that cooking facilities were rated low, while the laboratory environment, teacher supervision, and sustainability awareness were rated moderate. Students’ actual cooking performance was likewise low in preparation, production, and presentation. Multiple regression analysis revealed that cooking facilities significantly predicted cooking performance, while laboratory environment and sustainability awareness did not emerge as significant predictors. These results emphasize that functional, sufficient, and well-maintained kitchen equipment is foundational to effective experiential learning, consistent with Kolb’s Experiential Learning Theory and Moos’ Environmental Theory. Overall, the study underscores the need for improved facilities, stronger guided practice, and deeper integration of sustainability concepts in laboratory tasks to enhance students’ technical competence and engagement in cookery classes.